Unusual Infections Complicating the Use of Steroids with Severe Alcoholic Hepatitis: Report of 2 Cases - Vitor Arantes; Pina Michieletti; Ross Cameron; Jenny Heathcote; Morris Sherman (Canadian Journal of Gastroenterology)
Corticosteroid therapy for acute alcoholic hepatitis has been demonstrated to enhance survival in patients who are encephalopathic, and who do not have renal failure or gastrointestinal bleeding. However, the complications of steroid therapy in such patients have been less well documented. The authors report two patients with alcoholic liver disease who developed life-threatening infections after steroid therapy was started. The first patient initially developed diabetes followed by Fournier's gangrene of the perineum, and a lung abscess following septic emboli. The second patient had established alcoholic cirrhosis rather than alcoholic hepatitis. She developed a necrotic ulcer on the arm at the site of an intravenous line, which was infected with a rhizopus species. Despite surgical debridement the lesion progressed and contributed to her death. Treatment of alcoholic hepatitis with steroids is not innocuous, and physicians should be aware of the potential for life-threatening complications.